Sistem Pendukung Keputusan Pemilihan Tanaman Hortikultura Berdasarkan Karakteristik Lahan Menggunakan Metode Moora (Studi Kasus: Kabupaten Kepahiang) - Coastera, Funny Farady; Sari, Julia Purnama; Pasaribu, Bryan (Rekursif: Jurnal Informatika, 2024)
Indonesia is an agricultural country where almost all of its population works in the agricultural sector. Horticulture is one of the subsectors in agriculture that studies the cultivation of crops such as vegetables, fruits, medicinal plants and ornamental plants. Areas in Bengkulu Province, especially Kepahiang Regency, have people who are mostly farmers. The suitability of land with crops to be planted has an important role in increasing crop productivity. Of course, this method will not get maximum results. This encourages researchers to build a system that can provide decision assistance for farmers and communities in determining suitable crops for planting on a land in the Kepahiang Regency area. This decision support system was created using the MOORA method which consists of 17 land criteria and 35 horticultural crops. This system produces output in the form of ranking horticultural crops that are suitable for planting. The functionality testing process of this expert system went well using black box testing and resulted in 100% functional success. Evaluation of the accuracy of the MOORA method for ranking horticultural plants based on land characteristics resulted in an accuracy rate of 75%. Keywords: Horticulture, Decision Support System, MOORA Method, Land Characteristics.